Post-harvest tech drive - The Sun, (2012)
KUALA LUMPUR: The government will generate more initiatives and provide relevant incentives for the development of post-harvest technologies to boost agricultural production, said Deputy Prime Minister Tan Sri Muhyiddin Yassin.